Farm level natural capital accounting to connect on-ground agroforestry decision making with local and global imperatives: A case study in Tasmania, Australia - Daniel S. Mendham; Anthony O'Grady; Stephen Stewart; Jacqueline R. England; Suzanne M. Prober; Thomas Baker; Shaun Brooks; Martin Moroni; Chris Ware; Aysha Fleming; Stephen Roxburgh; Sue Ogilvy; et al. (Agricultural Systems, 2026)

Bridge to the future: Important lessons from 20 years of ecosystem observations made by the OzFlux network - Jason Beringer; Caitlin E. Moore; Jamie Cleverly; David I. Campbell; Helen Cleugh; Martin G. De Kauwe; Miko U. F. Kirschbaum; Anne Griebel; Sam Grover; Alfredo Huete; Lindsay B. Hutley; Johannes Laubach; et al. (Global Change Biology, 2022)
In 2020, the Australian and New Zealand flux research and monitoring network, OzFlux, celebrated its 20 th anniversary by reflecting on the lessons learned through two decades of ecosystem studies on global change biology. OzFlux is a network not only for ecosystem researchers, but also for those ‘next users’ of the knowledge, information and data that such networks provide. Here, we focus on eight lessons across topics of climate change and variability, disturbance and resilience, drought and heat stress and synergies with remote sensing and modelling. In distilling the key lessons learned, we also identify where further research is needed to fill knowledge gaps and improve the utility and relevance of the outputs from OzFlux. Extreme climate variability across Australia and New Zealand (droughts and flooding rains) provides a natural laboratory for a global understanding of ecosystems in this time of accelerating climate change. As evidence of worsening global fire risk emerges, the natural ability of these ecosystems to recover from disturbances, such as fire and cyclones, provides lessons on adaptation and resilience to disturbance. Drought and heatwaves are common occurrences across large parts of the region and can tip an ecosystem's carbon budget from a net CO 2 sink to a net CO 2 source. Despite such responses to stress, ecosystems at OzFlux sites show their resilience to climate variability by rapidly pivoting back to a strong carbon sink upon the return of favourable conditions. Located in under‐represented areas, OzFlux data have the potential for reducing uncertainties in global remote sensing products, and these data provide several opportunities to develop new theories and improve our ecosystem models. The accumulated impacts of these lessons over the last 20 years highlights the value of long‐term flux observations for natural and managed systems. A future vision for OzFlux includes ongoing and newly developed synergies with ecophysiologists, ecologists, geologists, remote sensors and modellers.

Combating ecosystem collapse from the tropics to the Antarctic - Dana M. Bergstrom; Barbara C. Wienecke; John van den Hoff; Lesley Hughes; David B. Lindenmayer; Tracy D. Ainsworth; Christopher M. Baker; Lucie Bland; David M. J. S. Bowman; Shaun T. Brooks; Josep G. Canadell; Andrew J. Constable; et al. (Global Change Biology, 2021)
Globally, collapse of ecosystems—potentially irreversible change to ecosystem structure, composition and function—imperils biodiversity, human health and well‐being. We examine the current state and recent trajectories of 19 ecosystems, spanning 58° of latitude across 7.7 M km 2 , from Australia's coral reefs to terrestrial Antarctica. Pressures from global climate change and regional human impacts, occurring as chronic ‘presses’ and/or acute ‘pulses’, drive ecosystem collapse. Ecosystem responses to 5–17 pressures were categorised as four collapse profiles—abrupt, smooth, stepped and fluctuating. The manifestation of widespread ecosystem collapse is a stark warning of the necessity to take action. We present a three‐step assessment and management framework (3As Pathway Awareness , Anticipation and Action ) to aid strategic and effective mitigation to alleviate further degradation to help secure our future.

Global impacts of fertilization and herbivore removal on soil net nitrogen mineralization are modulated by local climate and soil properties - Anita C. Risch; Stefan Zimmermann; Barbara Moser; Martin Schütz; Frank Hagedorn; Jennifer Firn; Philip A. Fay; Peter B. Adler; Lori A. Biederman; John M. Blair; Elizabeth T. Borer; Arthur A. D. Broadbent; et al. (Global Change Biology, 2020)
Soil nitrogen (N) availability is critical for grassland functioning. However, human activities have increased the supply of biologically limiting nutrients, and changed the density and identity of mammalian herbivores. These anthropogenic changes may alter net soil N mineralization (soil net N min ), that is, the net balance between N mineralization and immobilization, which could severely impact grassland structure and functioning. Yet, to date, little is known about how fertilization and herbivore removal individually, or jointly, affect soil net N min across a wide range of grasslands that vary in soil and climatic properties. Here we collected data from 22 grasslands on five continents, all part of a globally replicated experiment, to assess how fertilization and herbivore removal affected potential (laboratory‐based) and realized (field‐based) soil net N min . Herbivore removal in the absence of fertilization did not alter potential and realized soil net N min . However, fertilization alone and in combination with herbivore removal consistently increased potential soil net N min. Realized soil net N min , in contrast, significantly decreased in fertilized plots where herbivores were removed. Treatment effects on potential and realized soil net N min were contingent on site‐specific soil and climatic properties. Fertilization effects on potential soil net N min were larger at sites with higher mean annual precipitation (MAP) and temperature of the wettest quarter (T.q.wet). Reciprocally, realized soil net N min declined most strongly with fertilization and herbivore removal at sites with lower MAP and higher T.q.wet. In summary, our findings show that anthropogenic nutrient enrichment, herbivore exclusion and alterations in future climatic conditions can negatively impact soil net N min across global grasslands under realistic field conditions. This is an important context‐dependent knowledge for grassland management worldwide.

Microbial processing of plant remains is co‐limited by multiple nutrients in global grasslands - Raúl Ochoa‐Hueso; Elizabeth T. Borer; Eric W. Seabloom; Sarah E. Hobbie; Anita C. Risch; Scott L. Collins; Juan Alberti; Héctor A. Bahamonde; Cynthia S. Brown; Maria C. Caldeira; Pedro Daleo; Chris R. Dickman; et al. (Global Change Biology, 2020)
Microbial processing of aggregate‐unprotected organic matter inputs is key for soil fertility, long‐term ecosystem carbon and nutrient sequestration and sustainable agriculture. We investigated the effects of adding multiple nutrients (nitrogen, phosphorus and potassium plus nine essential macro‐ and micro‐nutrients) on decomposition and biochemical transformation of standard plant materials buried in 21 grasslands from four continents. Addition of multiple nutrients weakly but consistently increased decomposition and biochemical transformation of plant remains during the peak‐season, concurrent with changes in microbial exoenzymatic activity. Higher mean annual precipitation and lower mean annual temperature were the main climatic drivers of higher decomposition rates, while biochemical transformation of plant remains was negatively related to temperature of the wettest quarter. Nutrients enhanced decomposition most at cool, high rainfall sites, indicating that in a warmer and drier future fertilized grassland soils will have an even more limited potential for microbial processing of plant remains.

Nutrient availability controls the impact of mammalian herbivores on soil carbon and nitrogen pools in grasslands - Judith Sitters; E. R. Jasper Wubs; Elisabeth S. Bakker; Thomas W. Crowther; Peter B. Adler; Sumanta Bagchi; Jonathan D. Bakker; Lori Biederman; Elizabeth T. Borer; Elsa E. Cleland; Nico Eisenhauer; Jennifer Firn; et al. (Global Change Biology, 2020)
Grasslands are subject to considerable alteration due to human activities globally, including widespread changes in populations and composition of large mammalian herbivores and elevated supply of nutrients. Grassland soils remain important reservoirs of carbon (C) and nitrogen (N). Herbivores may affect both C and N pools and these changes likely interact with increases in soil nutrient availability. Given the scale of grassland soil fluxes, such changes can have striking consequences for atmospheric C concentrations and the climate. Here, we use the Nutrient Network experiment to examine the responses of soil C and N pools to mammalian herbivore exclusion across 22 grasslands, under ambient and elevated nutrient availabilities (fertilized with NPK + micronutrients). We show that the impact of herbivore exclusion on soil C and N pools depends on fertilization. Under ambient nutrient conditions, we observed no effect of herbivore exclusion, but under elevated nutrient supply, pools are smaller upon herbivore exclusion. The highest mean soil C and N pools were found in grazed and fertilized plots. The decrease in soil C and N upon herbivore exclusion in combination with fertilization correlated with a decrease in aboveground plant biomass and microbial activity, indicating a reduced storage of organic matter and microbial residues as soil C and N. The response of soil C and N pools to herbivore exclusion was contingent on temperature – herbivores likely cause losses of C and N in colder sites and increases in warmer sites. Additionally, grasslands that contain mammalian herbivores have the potential to sequester more N under increased temperature variability and nutrient enrichment than ungrazed grasslands. Our study highlights the importance of conserving mammalian herbivore populations in grasslands worldwide. We need to incorporate local‐scale herbivory, and its interaction with nutrient enrichment and climate, within global‐scale models to better predict land–atmosphere interactions under future climate change.

Belowground Biomass Response to Nutrient Enrichment Depends on Light Limitation Across Globally Distributed Grasslands - Elsa E. Cleland; Eric M. Lind; Nicole M. DeCrappeo; Elizabeth DeLorenze; Rachel Abbott Wilkins; Peter B. Adler; Jonathan D. Bakker; Cynthia S. Brown; Kendi F. Davies; Ellen Esch; Jennifer Firn; Scott Gressard; et al. (Ecosystems, 2019)

Sensitivity of global soil carbon stocks to combined nutrient enrichment - T. W. Crowther; C. Riggs; E. M. Lind; E. T. Borer; E. W. Seabloom; S. E. Hobbie; J. Wubs; P. B. Adler; J. Firn; L. Gherardi; N. Hagenah; K. S. Hofmockel; et al. (Ecology Letters, 2019)
Soil stores approximately twice as much carbon as the atmosphere and fluctuations in the size of the soil carbon pool directly influence climate conditions. We used the Nutrient Network global change experiment to examine how anthropogenic nutrient enrichment might influence grassland soil carbon storage at a global scale. In isolation, enrichment of nitrogen and phosphorous had minimal impacts on soil carbon storage. However, when these nutrients were added in combination with potassium and micronutrients, soil carbon stocks changed considerably, with an average increase of 0.04 KgCm −2 year −1 (standard deviation 0.18 KgCm −2 year −1 ). These effects did not correlate with changes in primary productivity, suggesting that soil carbon decomposition may have been restricted. Although nutrient enrichment caused soil carbon gains most dry, sandy regions, considerable absolute losses of soil carbon may occur in high‐latitude regions that store the majority of the world's soil carbon. These mechanistic insights into the sensitivity of grassland carbon stocks to nutrient enrichment can facilitate biochemical modelling efforts to project carbon cycling under future climate scenarios.

Herbivory and eutrophication mediate grassland plant nutrient responses across a global climatic gradient - T. Michael Anderson; Daniel M. Griffith; James B. Grace; Eric M. Lind; Peter B. Adler; Lori A. Biederman; Dana M. Blumenthal; Pedro Daleo; Jennifer Firn; Nicole Hagenah; W. Stanley Harpole; Andrew S. MacDougall; et al. (Ecology, 2018)
Plant stoichiometry, the relative concentration of elements, is a key regulator of ecosystem functioning and is also being altered by human activities. In this paper we sought to understand the global drivers of plant stoichiometry and compare the relative contribution of climatic vs. anthropogenic effects. We addressed this goal by measuring plant elemental (C, N, P and K) responses to eutrophication and vertebrate herbivore exclusion at eighteen sites on six continents. Across sites, climate and atmospheric N deposition emerged as strong predictors of plot‐level tissue nutrients, mediated by biomass and plant chemistry. Within sites, fertilization increased total plant nutrient pools, but results were contingent on soil fertility and the proportion of grass biomass relative to other functional types. Total plant nutrient pools diverged strongly in response to herbivore exclusion when fertilized; responses were largest in ungrazed plots at low rainfall, whereas herbivore grazing dampened the plant community nutrient responses to fertilization. Our study highlights (1) the importance of climate in determining plant nutrient concentrations mediated through effects on plant biomass, (2) that eutrophication affects grassland nutrient pools via both soil and atmospheric pathways and (3) that interactions among soils, herbivores and eutrophication drive plant nutrient responses at small scales, especially at water‐limited sites.

Spatial structuring of arbuscular mycorrhizal communities in benchmark and modified temperate eucalypt woodlands - Suzanne M. Prober; A. Bissett; C. Walker; G. Wiehl; S. McIntyre; M. Tibbett (Mycorrhiza, 2015)

Plant diversity predicts beta but not alpha diversity of soil microbes across grasslands worldwide - Suzanne M. Prober; Jonathan W. Leff; Scott T. Bates; Elizabeth T. Borer; Jennifer Firn; W. Stanley Harpole; Eric M. Lind; Eric W. Seabloom; Peter B. Adler; Jonathan D. Bakker; Elsa E. Cleland; Nicole M. DeCrappeo; et al. (Ecology Letters, 2015)
Aboveground–belowground interactions exert critical controls on the composition and function of terrestrial ecosystems, yet the fundamental relationships between plant diversity and soil microbial diversity remain elusive. Theory predicts predominantly positive associations but tests within single sites have shown variable relationships, and associations between plant and microbial diversity across broad spatial scales remain largely unexplored. We compared the diversity of plant, bacterial, archaeal and fungal communities in one hundred and forty‐five 1 m 2 plots across 25 temperate grassland sites from four continents. Across sites, the plant alpha diversity patterns were poorly related to those observed for any soil microbial group. However, plant beta diversity (compositional dissimilarity between sites) was significantly correlated with the beta diversity of bacterial and fungal communities, even after controlling for environmental factors. Thus, across a global range of temperate grasslands, plant diversity can predict patterns in the composition of soil microbial communities, but not patterns in alpha diversity.

Anthropogenic‐based regional‐scale factors most consistently explain plot‐level exotic diversity in grasslands - Andrew S. MacDougall; Joseph R. Bennett; Jennifer Firn; Eric W. Seabloom; Elizabeth T. Borer; Eric M. Lind; John L. Orrock; W. Stanley Harpole; Yann Hautier; Peter B. Adler; Elsa Cleland; Kendi Davies; et al. (Global Ecology and Biogeography, 2014)
Aim Evidence linking the accumulation of exotic species to the suppression of native diversity is equivocal, often relying on data from studies that have used different methods. Plot‐level studies often attribute inverse relationships between native and exotic diversity to competition, but regional abiotic filters, including anthropogenic influences, can produce similar patterns. We seek to test these alternatives using identical scale‐dependent sampling protocols in multiple grasslands on two continents. Location Thirty‐two grassland sites in N orth A merica and A ustralia. Methods We use multiscale observational data, collected identically in grain and extent at each site, to test the association of local and regional factors with the plot‐level richness and abundance of native and exotic plants. Sites captured environmental and anthropogenic gradients including land‐use intensity, human population density, light and soil resources, climate and elevation. Site selection occurred independently of exotic diversity, meaning that the numbers of exotic species varied randomly thereby reducing potential biases if only highly invaded sites were chosen. Results Regional factors associated directly or indirectly with human activity had the strongest associations with plot‐level diversity. These regional drivers had divergent effects: urban‐based economic activity was associated with high exotic : native diversity ratios; climate‐ and landscape‐based indicators of lower human population density were associated with low exotic : native ratios. Negative correlations between plot‐level native and exotic diversity, a potential signature of competitive interactions, were not prevalent; this result did not change along gradients of productivity or heterogeneity. Main conclusion We show that plot‐level diversity of native and exotic plants are more consistently associated with regional‐scale factors relating to urbanization and climate suitability than measures indicative of competition. These findings clarify the long‐standing difficulty in resolving drivers of exotic diversity using single‐factor mechanisms, suggesting that multiple interacting anthropogenic‐based processes best explain the accumulation of exotic diversity in modern landscapes.

Predicting invasion in grassland ecosystems: is exotic dominance the real embarrassment of richness? - Eric W. Seabloom; Elizabeth T. Borer; Yvonne Buckley; Elsa E. Cleland; Kendi Davies; Jennifer Firn; W. Stanley Harpole; Yann Hautier; Eric Lind; Andrew MacDougall; John L. Orrock; Suzanne M. Prober; et al. (Global Change Biology, 2013)
Invasions have increased the size of regional species pools, but are typically assumed to reduce native diversity. However, global‐scale tests of this assumption have been elusive because of the focus on exotic species richness, rather than relative abundance. This is problematic because low invader richness can indicate invasion resistance by the native community or, alternatively, dominance by a single exotic species. Here, we used a globally replicated study to quantify relationships between exotic richness and abundance in grass‐dominated ecosystems in 13 countries on six continents, ranging from salt marshes to alpine tundra. We tested effects of human land use, native community diversity, herbivore pressure, and nutrient limitation on exotic plant dominance. Despite its widespread use, exotic richness was a poor proxy for exotic dominance at low exotic richness, because sites that contained few exotic species ranged from relatively pristine (low exotic richness and cover) to almost completely exotic‐dominated ones (low exotic richness but high exotic cover). Both exotic cover and richness were predicted by native plant diversity (native grass richness) and land use (distance to cultivation). Although climate was important for predicting both exotic cover and richness, climatic factors predicting cover (precipitation variability) differed from those predicting richness (maximum temperature and mean temperature in the wettest quarter). Herbivory and nutrient limitation did not predict exotic richness or cover. Exotic dominance was greatest in areas with low native grass richness at the site‐ or regional‐scale. Although this could reflect native grass displacement, a lack of biotic resistance is a more likely explanation, given that grasses comprise the most aggressive invaders. These findings underscore the need to move beyond richness as a surrogate for the extent of invasion, because this metric confounds monodominance with invasion resistance. Monitoring species' relative abundance will more rapidly advance our understanding of invasions.

Combining community-level spatial modelling and expert knowledge to inform climate adaptation in temperate grassy eucalypt woodlands and related grasslands - Suzanne M. Prober; D. W. Hilbert; S. Ferrier; M. Dunlop; D. Gobbett (Biodiversity and Conservation, 2012)